Is English Teaching and Learning Effective through Blended Approach in Bangladesh? An Empirical Study - Hoque, Emdadul; Hossain, Md Akhtar (Mother Language, 2025)
This empirical study identifies important elements impacting the deployment of blended learning and investigates its efficacy in English teaching throughout Bangladesh. Correlation analysis showed that usage frequency, teaching experience, and participant categorization all had a substantial impact on how successful blended learning was regarded, with younger or less experienced instructors showing superior conceptual knowledge. Regression analysis revealed that while skill improvement alone was not a significant predictor, knowledge of blended learning was significantly correlated with active involvement, institutional support, and teacher engagement. A thorough, multifaceted strategy is necessary for blended English language training in Bangladesh to be successful, according to the findings. The basis must be a strong digital infrastructure, first and foremost. This has to be followed by consistent funding for teacher preparation, student assistance programs, better internet access, and the thoughtful integration of cutting-edge technology like machine learning. It will need concerted efforts from legislators, schools, IT companies, and community stakeholders to accomplish these objectives. Blended learning in Bangladesh cannot develop into an inclusive, long-lasting, and significant educational paradigm without such cooperation. According to the study’s f indings, a comprehensive and inclusive strategy is necessary for long-term success. This strategy combines innovations in education delivery, pedagogical training, institutional support, learner support, and technology advancements to guarantee fair and efficient blended English instruction in Bangladesh. Mother Language, 2025; 9(1): 44-72